ANALISIS EFISIENSI PADA PELAYANAN PENGEMBANGAN KOMPETENSI MENGGUNAKAN METODE BUSINESS PROCESS IMPROVEMENT (STUDI KASUS: BKPSDM PROVINSI BALI) - Amar Ma'ruf; Raulia Riski; Hawwin Mardhiana (Program Studi Sistem Informasi, Universitas Banten Jaya, 2024)
Human Resources (HR) play a crucial role in service delivery. Improving HR quality builds public trust in the government, making HR a critical factor in an organization's success. Kerti Bali Sejahtera Corporate University (KBS CorpU) is a system currently being developed by the BKPSDM Bali Team to enhance the Professional Index (PI) and Competency of Civil Servants (ASN) and Non-Civil Servants (Non-ASN) in Bali Province. This application is targeted to be operational in 2024 to demonstrate its effectiveness in enhancing Civil Servant competency. However, there is currently no efficiency data on the Competency Development (CD) process to review the performance of PI and ASN competencies, which contradicts Article 55 of Law No. 5 of 2014. This study aims to simplify the current business process (as-is) and improve the recommended business process (to-be) to analyze the efficiency of the to-be CD process, determining the readiness and success of this application in improving ASN performance in Bali. The Business Process Improvement (BPI) method is used to identify time analysis on the as-is and to-be CD processes through value chain analysis, process decomposition, and PICK chart. Time efficiency is calculated using the Efficiency Improvement Value (NPE) formula. The results show that the to-be CD process provides time efficiency with a business strategy improvement of 52.13%, activity reduction of 45%, and document reduction of 100%. This proves the readiness and success of the KBS CorpU application in the coming year, enabling it to improve the PI and competency of ASN/Non-ASN in Bali Province, in accordance with Law No. 5 of 2014 concerning Civil Servants.